Penggunaan Make Up Sebagai Bentuk Citra Diri Generasi Z: (Studi Fenomenologi Terhadap Citra Diri Mahasiswi Fakultas Ilmu Komunikasi Universitas Islam Bandung) - Yunda Melyanita; Neni Yulianita (UNISBA Press, 2023)
Abstract. Generation Z is known for a generation that attaches great importance to appearance compared to other things, and a female college student is no exception. As social actors, generation Z certainly has its own motives, experiences and meanings in shaping self image. In this case, one of the efforts made is to use makeup in daily activities. By using qualitative research methods from Alfred Schutz's phenomenological study approach, researchers tried to achieve the research objectives of how the phenomenon of using makeup as a form of self-image in UNISBA Communication Science students as generation Z by exploring the motives, experiences, and meanings of using makeup. The results showed that generation Z has a motive, experience, and meaning for the use of makeup. Motives themselves are divided into because motive and in order motive. The findings of the motive itself are the motive for technological development (social media), environmental motives, insecure motives, and self confidence motives. While the findings of in-order motive, namely the first impression motive, happy motives to be the center of attention, and career motives. With the motive at hand, Generation Z often gets praise, no longer finds comments about physical imperfections, and is often the center of attention. The meaning of using makeup for generation Z's self image is not only limited to makeup, but a form of effort to improve self quality, both in terms of appearance and expression of feelings in social life. Abstrak. Generasi Z dikenal dengan generasi yang sangat mementingkan penampilan dibandingkan dengan hal lain, tidak terkecuali seorang mahasiswi. Sebagai pelaku sosial, generasi Z tentunya memiliki motif, pengalaman dan makna tersendiri dalam membentuk citra diri. Dalam hal ini salah satu upaya yang dilakukan adalah menggunakan make up dalam berkegiatan sehari-hari. Dengan menggunakan metode penelitian kualitatif pendekatan studi fenomenologi Alfred Schutz ini, peneliti berusaha untuk mencapai tujuan penelitian mengenai bagaimana fenomena penggunaan make up sebagai salah satu bentuk citra diri pada mahasiswi Ilmu Komunikasi UNISBA selaku generasi Z dengan cara menggali motif, pengalaman, dan makna penggunaan make up. Hasil penelitian menunjukkan generasi Z memiliki motif, pengalaman, dan makna terhadap penggunaan make up. Motif sendiri terbagi menjadi because motive dan in order motive. Temuan because motive sendiri yakni motif perkembangan teknologi (social media), motif lingkungan, motif insecure, dan motif rasa percaya diri. Sedangkan temuan in order motive, yakni motif first impression, motif senang menjadi pusat perhatian, dan motif karir. Dengan motif yang ada, generasi Z kerap memperoleh pujian, tidak lagi mendapati komentar mengenai ketidaksempurnaan fisik, dan sering menjadi pusat perhatian. Makna penggunaan make up bagi citra diri generasi Z bukan hanya sebatas riasan wajah, tetapi bentuk upaya peningkatan kualitas diri, baik dalam segi penampilan ataupun ungkapan perasaan dalam berkehidupan sosial.